Impact of oil rents, oil prices, and investment taxes on renewable energy consumption and investment: An investigation - Makki, Mohammad; Mawad, Jeanne Laure; Khalili, Mira (International Journal of Management and Sustainability, 2023)
The aim of this paper is to explore the relationship between oil rents and renewable energy consumption and to provide evidence on the significance of the effects of oil prices and investment taxes on renewable energy investment. Two different panel data samples were used: six variables for 44 countries were utilized to prove that oil rents’ are an independent variable causing renewable energy consumption, and five variables for 10 countries were utilized to prove that higher oil prices and higher investment taxes lead to higher levels of renewable energy investment. For both samples, the Granger causality test, unit root test, correlation matrix, fixed and random multiple regressions, Hausman test, and panel cointegration test were performed. The paper adds to the narrow literature on the determinants of renewable energy consumption, mainly oil rents. It also provides further evidence on how higher investment taxes can lead to higher renewable energy investment. The findings confirm that “oil rents” directly affect the variations in renewable energy consumption and that investment taxes directly affect renewable energy investment as they lead to a higher selling price of oil-dependent products. However, no correlation was found between renewable energy investment and oil prices. Taxes are an effective instrument for changing people’s and businesses’ behaviour. Given the numerous advantages of renewable energy consumption and investment, governments must make plans and create regulations and laws to compel a gradual transition from non-renewable to renewable energy using consumption and investment taxes and other behavioral incentives.